MAKNA LAGU ARA DALAM RITUAL PENTI PADA GUYUP TUTUR ETNIK MANGGARAIAN DI FLORES - BUSTAN, FRANSISKUS (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2008)
Abstract This study examines the meanings of Ara folksong in the context of penti ritual or traditional new year party in the speech community of Manggarai ethnic group in Flores. In accordance with the characteristics of its linguistic units, the meanings implied and stated in Ara folksong cover religious, sociologic, and aesthetic meaning. The religious meaning deals with the belief system shared by the speech community of Manggarai ethnic group on the existence of the Supreme God, their ancestors, and the environmental spirits. The sociologic meaning is related to social value on the importance of unity in favor of maintaining cohesive social relationship. The aesthetic meaning is concerned with formal and sensual values, which cover behind them socio-religious value functioning as moral and ethic guideline for the speech community of Manggarai ethnic group.